Evaluation of SRAP marker efficiency in identifying the relationship between genetic diversities of corn inbred lines with seed quantity and quality in derived hybrids - Fareghi, Sharareh; Mirlohi, Agha Fakhr; Saeidi, Ghodratollah; Khamisabadi, Hassan (Cellular and Molecular Biology, 2019)
In order to estimate the efficiency of SRAP markers for identifying the performance of seed quantity and quality in maize single crosses, 13 inbred lines obtained from CIMMYT germplasm bank were crossed to A679, K166B, K18 and MO17 testers using the lineí—tester method. The inbred lines and derived hybrids were evaluated in two experiments separately in a randomized complete block design with three replications during two growing seasons in 2014 and 2015. In order to evaluate genetic variation in the inbred lines, 25 SRAP markers were also used. The results of variance analysis between inbred lines were showed a significant variation (Pâ‰¤0.01) for seed quantity and quality. The analysis of variance among the hybrids derived from inbred lines was showed a significant variation (Pâ‰¤0.01) for oil percent, starch content, protein content, seed yield and thousand seed weights and a significant variation for the dry matter (Pâ‰¤0.05). The maximum Euclidian distance between the two lines was 24.5 times greater than the minimum distance between two lines. The PCR amplification for the 17 parentallines with the 25 combinations of SRAP primers generated a total of 205 clear and scorable bands, of which 135 were polymorphic (65.75%). The average distance between the studied lines was 0.324 on the bases of the Jaccard coefficient and maximum distance between two lines was 2.87 times greater than the minimum distance between two lines. The M1E1, M1E5, M5E3, M5E4, and M5E5 were superior to other primer combinations in expressing genetic diversity based on the primer information indices. The banding pattern of the studied primer combinations related to the genetic variation of the inbred lines based on the studied traits revealed that the M5E1 primer pair can predict the distance of inbred lines for dry matter better than other primers. Also, the primers combination of M4E4 for protein percentage, M4E4 for starch percentage, M2E3 for crude fiber, M4E3 for oil percentage, M2E5, M4E1 and M5E1 for thousand seed weight and M3E1 for seed yield, can be introduced as informative primer combination, to estimate genetic distance determination of inbred lines based on these traits. Due to the relationship between inbred lines variation based on primers combinations with the traits in hybrids progenies showed that the M2E1, M2E2, M4E1 and M5E3 for dry matter and M2E4 for starch percentage have the ability to detect hybrid performance for these traits. For traits, protein percentage, crude fiber and oil percent no suitable primers combination were found. Also, for the seed yield, three primer combinations of M1E5, M2E2 and M3E2 had the highest negative correlation. Therefore, the hybrids derived from the inbred lines with high genetic distance based on these primers combinations will have a low seed yield. The M1E2, M2E3 and M5E5 can be introduced to identify the prediction of higher thousand seed weight.